Shored up [videorecording (DVD)] - Kalina, Ben; Hogan, Paul Damian, 1976- (Outcast Films : [Philadelphia, Pa.] : Mangrove Media, 2013)
Portrays the complex relationship between humans and the environment, particularly the social, economic, and ecological issues. Focusing on the tragedy of Hurricane Sandy, interprets the depths of these multiple perspectives.